2019
DOI: 10.1002/eap.1901
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem service change caused by climatological and non‐climatological drivers: a Swiss case study

Abstract: Understanding the drivers of ecosystem change and their effects on ecosystem services are essential for management decisions and verification of progress towards national and international sustainability policies (e.g., Aichi Biodiversity Targets, Sustainable Development Goals). We aim to disentangle spatially the effect of climatological and non‐climatological drivers on ecosystem service supply and trends. Therefore, we explored time series of three ecosystem services in Switzerland between 2004 and 2014: ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Slope data are generated from elevation, and the influence of these geographic features on ESVs is also important [ 40 , 45 , 75 ]. The effects of temperature and precipitation on ESVs vary with geographic location [ 76 ]. In addition, population density and economic factors also have important effects on ESVs [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Slope data are generated from elevation, and the influence of these geographic features on ESVs is also important [ 40 , 45 , 75 ]. The effects of temperature and precipitation on ESVs vary with geographic location [ 76 ]. In addition, population density and economic factors also have important effects on ESVs [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Water yield changes were mainly attributed to climate change, while soil retention was largely influenced by interactions. Recent studies noted that precipitation patterns directly determine water yield, especially in mountainous areas, where precipitation is the main recharge (Braun et al, 2019). For example, Yin et al (2022) found that water yield changes in North China were more sensitive to precipitation than temperature, and the changes demonstrated a trend consistent with the precipitation change from 1995 to 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Natural factors, such as elevation (ELEV), slope (SLOPE), precipitation (PRE), and temperature (TEM), directly affect the formation and spatial distribution of ESs by altering the regional material cycle and energy flow (Blake et al, 2021). Climate drivers such as TEM, PRE and relative sunshine duration strongly influence ecosystem service trends in Switzerland (Braun et al, 2019). The influence of each factor on different types of ESs varies in China and the Jiangsu coastal areas.…”
Section: Introductionmentioning
confidence: 99%